Mixed-Fungi Applications Enhance Litter Decomposition More Strongly in the Soil Profile than on the Ground in a Desert Steppe Ecosystem, Northwestern China - Hao Qu; Meixin Wang; Jing Wu; Guolin Wang; Ming Zhang; Gang Han; Salman Zare; Eduardo Medina-Roldán (Pedobiologia, 2026)

Distinct ecology patterns of bacterial generalists and specialists provide fresh insights into the management of ship ballast sediments - Baoyi Lv; Shenglong Mei; Guolin Kan; Yangchun Han; Changhai Jiang; Yuxue Cui; Jianhong Shi (Marine Pollution Bulletin, 2026)

Metagenomics insights into the functional traits and risk surveillance of ballast water microbiome from a genome-centric perspective - Baoyi Lv; Guolin Kan; Shenglong Mei; Yangchun Han; Changhai Jiang; Yuxue Cui; Jianhong Shi (Process Safety and Environmental Protection, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Uncovering the gut microbiome and antibiotic resistome of mammals on the Tibetan Plateau - Chen Tian; Zecheng Tang; Xiaoyu Zhang; Xueqin Yao; Yitian Li; Daohua Zhuang; Yu Luo; Teng Li; Liyan Bai; Fangfang Zhao; Lei Zhu; Guolin Shi; et al. (Science China Life Sciences, 2025)

Exploring Facial Nucleus-Centered Connectivity in Hemifacial Spasm: Novel Insights into Pathogenesis and Surgical Impact - Yu Duan; Kuan Lv; Chao Zhao; Liangbo Han; Jianke Wang; Chuanpeng Zhang; Ziyi Zhang; Hanlin Liu; Ke Yang; Zhen Yuan; Li Zhu; Yuli Wang; et al. (Brain Topography, 2025)

The abrupt rise of midsummer high-temperature days and surface air temperature in Southern China around the early 2000s and it’s influences on climate forecasts - Zikang Jia; Guolin Feng; Zhisen Zhang; Han Zhang; Naihui Zang; Zhihai Zheng (Climate Dynamics, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Monitoring of surface deformation in mining area integrating SBAS InSAR and Logistic Function - Fengyun Wang; Qiuxiang Tao; Guolin Liu; Yang Chen; Yu Han; Zaijie Guo; Xiaoshuai Liu (Environmental Monitoring and Assessment, 2023)

Extreme precipitation driven by the rapid tropical Atlantic warming and the second developing La Niña over the Yangtze–Huaihe River Basin in August 2021 - Junhu Zhao; Jinqing Zuo; Han Zhang; Lijuan Chen; Jie Yang; Zheng Zhihai; Guolin Feng (Climate Dynamics, 2023)

Dominant modes and mechanisms of atmospheric rivers in East Asia - Shulin Qu; Tao Su; Zixuan Han; Bicheng Huang; Guolin Feng (Atmospheric Research, 2023)

Correction to: Oceanic drivers and empirical prediction of interannual rainfall variability in late summer over Northeast China - Junhu Zhao; Han Zhang; Jinqing Zuo; Liu Yang; Jie Yang; Kaiguo Xiong; Guolin Feng; Wenjie Dong (Climate Dynamics, 2023)

Impacts of El Niño–Southern Oscillation on tropical precipitation via triggering anomaly water vapour transport from ocean to land - Jialin Wang; Feifei Pan; Haiyan Li; Pingli An; Guolin Han; Kang Jiang; Xiao Chen; Ziyuan Zhang; Yu Song; Na Huang; Shangqian Ma; Zhenzhen Zhang; et al. (International Journal of Climatology, 2023)
Atmospheric water vapour transport is one of the most active components of the hydrological cycle, which shows great effects on the regional climate variability, while it is largely affected by the large‐scale circulation systems. El Niño–Southern Oscillation (ENSO) shows a remarkable influence on the atmospheric water circulation via disrupting the normal/regular water vapour transport processes, producing the anomaly water vapour fluxes input from ocean to land ( Q net ), and leading to regional precipitation anomalies. However, their quantitative impact has not been fully studied. This study quantified the effect of ENSO on the water vapour transport from ocean to land and identified its impact on tropical precipitation anomalies. The results showed that the global detrended Q net displayed a significantly negative correlation with the strength of ENSO. The notable impact of ENSO on Q net was largely affected by the different patterns of the atmospheric moisture circulation during El Niño and La Niña and was responsible for the change of the spatial distribution of precipitation over the Tropics. El Niño reduced precipitation over the Malay Archipelago and increased precipitation over south China, especially in boreal winter, while La Niña enhanced precipitation over the Malay Archipelago. This study identified the impacts of ENSO on the circulation and water vapour transport process and improved our understanding of the influencing mechanism of ENSO on regional precipitation anomalies, which has important significance on regional water resource management and disaster risk assessment, especially as the extreme climate events have become increasingly frequent.

Mechanisms responsible for interdecadal variation of the thermodynamic component of East Asian summer monsoon moisture transport - Tao Su; Yue Li; Bicheng Huang; Shulin Qu; Zixuan Han; Zhonghua Qian; Guolin Feng; Yongping Wu (International Journal of Climatology, 2022)
In this study, the East Asian summer (June–July–August) monsoon (EASM) atmospheric moisture transport variability under global warming are examined using ERA‐Interim reanalysis data from 1979 to 2019. The total EASM atmospheric moisture transport is decomposed into the thermodynamic (δTH) and dynamic (δMCD) components, which are related to specific humidity and wind velocity, respectively. Based on empirical orthogonal function (EOF) analysis, both the second and the fourth modes of δTH are linked to δMCD, indicating that δMCD can impact the moisture distribution and consequently influence δTH indirectly. Both the first (δTH_EOF1) and the third (δTH_EOF3) modes of δTH show considerable interdecadal changes. It is noted that their principal components exhibit significant increasing trends in recent decades. The response of EASM moisture transport to global warming is probably reflected in these two modes. δTH_EOF1 is associated with negative phases of the Interdecadal Pacific Oscillation (IPO)/Pacific Decadal Oscillation (PDO). This causes the western North Pacific subtropical high (WNPSH) to extend westward and the strengthening of Pacific trade winds. As a result, positive precipitable water anomalies dominate East Asia and δTH_EOF1 is characterized by anomalous southwesterly moisture transport along the East China Sea to southern Japan. δTH_EOF3 corresponds to anomalous moisture transport over the Indochina Peninsula and Japan. The precipitable water associated with δTH_EOF3 in general represents a meridional dipole. Anomalous southward wind induced by the eastward extension of the WNPSH is the main reason for positive (negative) precipitable water anomalies in southern (northern) East Asian. The anomalous circulation associated with the anomalous east–west sea surface temperature gradient over the Indian Ocean affects atmospheric moisture in southern East Asian and can dramatically impact δTH_EOF3.

The variabilities of convective precipitation and large-scale precipitation in southern China for the period 1980–2020 - Han Zhang; Junhu Zhao; Bicheng Huang; Naihui Zang; Jie Yang; Guolin Feng (Theoretical and Applied Climatology, 2022)

The adaptation mechanism based on an integrated vulnerability assessment of potato production to climate change in Inner Mongolia, China - Na Huang; Jialin Wang; Yu Song; Yuying Pan; Guolin Han; Ziyuan Zhang; Shangqian Ma; Guofeng Sun; Cong Liu; Zhihua Pan (Mitigation and Adaptation Strategies for Global Change, 2022)

Oceanic drivers and empirical prediction of interannual rainfall variability in late summer over Northeast China - Junhu Zhao; Han Zhang; Jinqing Zuo; Liu Yang; Jie Yang; Kaiguo Xiong; Guolin Feng; Wenjie Dong (Climate Dynamics, 2022)

Long‐term mean changes in actual evapotranspiration over China under climate warming and the attribution analysis within the Budyko framework - Tao Su; Taichen Feng; Bicheng Huang; Zixuan Han; Zhonghua Qian; Guolin Feng; Wei Hou; Wenjie Dong (International Journal of Climatology, 2022)
In this study, the temporal variation of actual evapotranspiration (AE) over China during 1980–2015 is analysed based on an ensemble of six reanalyses and a complementary‐relationship‐based AE dataset. The results reveal that annual mean AE in China increases significantly, and the major regime shift occurred around 1998. Accordingly, long‐term mean AE changes from 1999–2015 relative to 1980–1997 are computed to quantify the spatial pattern of AE trends. In general, annual AE increases significantly in southern and northwestern China but decreases significantly in northeastern China and eastern Tibetan Plateau. Then we examine the primary cause for changes in AE using the Budyko framework, in which the change of climate is represented by changes in precipitation and potential evapotranspiration and the shift in landscape characteristics is represented by the parameter n . Overall, increasing potential evapotranspiration is the main contributor to the increase of AE in southeastern China. Increasing potential evapotranspiration and the parameter n are the main contributors to the increase of AE in southwestern China. Decreasing AE in northeastern China and eastern Tibetan Plateau are respectively caused by changes in precipitation and the parameter n , whereas the combination of these two factors has led to increasing AE in northwestern China. It is shown here that the contribution of the parameter n is comparable to that of climate change in western China. A positive correlation is found between vegetation coverage and the parameter n ; however, vegetation type, catchment slope, irrigation practices, and glacial meltwater also have an impact on regional n . A concurrent occurrence of the negative contribution of parameter n and positive vegetation coverage change is found in the forest land of northeastern and southeastern China. Decreasing irrigation water is likely the main reason for the negative contribution of n in cropland of the North China Plain.

Interdecadal variations of persistent extreme heat events in eastern China under global warming - Naihui Zang; Junhu Zhao; Pengcheng Yan; Han Zhang; Shankai Tang; Guolin Feng (Theoretical and Applied Climatology, 2021)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

The changes in ENSO-induced tropical Pacific precipitation variability in the past warm and cold climates from the EC-Earth simulations - Zixuan Han; Qiong Zhang; Qin Wen; Zhengyao Lu; Guolin Feng; Tao Su; Qiang Li; Qiang Zhang (Climate Dynamics, 2020)
The El Niño-Southern Oscillation (ENSO) is one of the most significant climate variability signals. Studying the changes in ENSO-induced precipitation variability (ENSO precipitation) in the past climate offers a possibility to a better understanding of how they may change under future climate conditions. This study uses simulations performed with the European community Earth-System Model (EC-Earth) to investigate the relative contributions of dynamic effect (the circulation anomalies together with the climatological specific humidity) and thermodynamic effect (the specific humidity anomalies together with the climatological circulation) on the changes in ENSO precipitation in the past warm and cold climates, represented by the Pliocene and the Last Glacial Maximum (LGM), respectively. The results show that the changes in ENSO precipitation are intensified (weakened) over the tropical western Pacific but weakened (intensified) over the tropical central Pacific in Pliocene (LGM) compared with the pre-industrial (PI) simulation. Based on the decomposed moisture budget equation, these changes in ENSO precipitation patterns are highly related to the dynamic effect. The mechanism can be understood as follows: the zonal gradient of the mean sea surface temperature (SST) over the tropical Indo-Pacific is increased (reduced) during the Pliocene (LGM), leading to the strengthening (weakening) of Pacific Walker Circulation as well as a westward (eastward) shift. In the Pliocene, the westward shift of Walker Circulation results in an increased (decreased) ENSO-induced low-level vertical velocity variability in the tropical western Pacific (central Pacific), and, in turn, favoring convergent (divergent) moisture transport through a dynamic process, and then causing intensified (weakened) ENSO precipitation there. The opposite mechanism exists in LGM. These results suggest that changes in the zonal SST gradient over tropical Indo-Pacific under different climate conditions determine the changes in ENSO precipitation through a dynamic process.

Thermodynamic and dynamic effects of increased moisture sources over the Tropical Indian Ocean in recent decades - Zixuan Han; Tao Su; Qiong Zhang; Qin Wen; Guolin Feng (Climate Dynamics, 2019)

Changes in global monsoon precipitation and the related dynamic and thermodynamic mechanisms in recent decades - Zixuan Han; Tao Su; Bicheng Huang; Taichen Feng; Shulin Qu; Guolin Feng (International Journal of Climatology, 2019)
The aim of this study is to explore the long‐term trends in the distribution of global monsoon precipitation over recent decades using the Global Precipitation Climatology Project (GPCP) data set. In addition, the potential4 mechanisms are examined by applying the atmospheric moisture budget decomposition method to the outputs from the ERA‐Interim medium‐range weather forecasting reanalysis produced by the European Centre for Medium‐Range Weather Forecasts (ECMWF). Changes in global monsoon precipitation are primarily thermodynamically caused by changes in specific humidity and dynamically caused by changes in circulation, as well as by changes in moisture transport that are driven by transient eddies and local evaporation. The results show that the increasing trends in global summer monsoon precipitation from 1979 to 2016 were dominated by contributions from the southern Asian, South African, and North American monsoon regions and were driven by the response of atmospheric circulation to the enhanced east–west thermal contrast in the tropical Pacific. We find that changes in the sea surface temperature (SST) patterns promote increased low‐level vertical velocities in monsoon regions, leading to moisture convergence through divergent circulation anomalies when combined with the climatological humidity field. Hence, the processes result in increasing trends in monsoon precipitation. In addition, evaporation makes increasing contributions to monsoon precipitation throughout the world, except in the South American monsoon region. Moreover, subtropical regions in the East Pacific (the Atlantic) may be major sources of water vapour that have supported increases in precipitation over the southern Asian and North American monsoon regions (the South African monsoon region) in recent decades.

A quantitative method for determining the impact threshold of climate change for agriculture - Zhiqiang Dong; Zhihua Pan; Pingli An; Jialin Wang; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dongliang Fan; Dong Wu; et al. (Theoretical and Applied Climatology, 2019)

Enhancement of the relationship between the winter Arctic oscillation and the following summer circulation anomalies over central East Asia since the early 1990s - Shaobo Qiao; Po Hu; Taichen Feng; Jianbo Cheng; Zixuan Han; Zhiqiang Gong; Rong Zhi; Guolin Feng (Climate Dynamics, 2018)

A quantitative method for risk assessment of agriculture due to climate change - Zhiqiang Dong; Zhihua Pan; Pingli An; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dong Wu; Jialin Wang; Dongliang Fan; et al. (Theoretical and Applied Climatology, 2018)

Basin modeling in the initial stage of exploration: a case study from the North Subbasin of the South Yellow Sea Basin - Yumao Pang; Xunhua Zhang; Xingwei Guo; Guolin Xiao; Zuozhen Han (Acta Oceanologica Sinica, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)